Lessons learned from teaching social justice education in sixth grade. Issue 5 (20th October 2022) - DeMink-Carthew, Jessica; Gonell, Eliaquin
Abstract: Early adolescence is a dynamic stage for the development of critical consciousness, yet there are few resources focused on social justice education (SJE) in the middle grades. This article shares the findings from a study that investigated the experiences of three social justice educators as they engaged in SJE with young adolescents (YAs). We offer three key lessons associated with teaching SJE in the middle grades: (a) YAs are primed for SJ learning, (b) SJE can cultivate a learner-centered classroom community, and (c) SJE brings teacher positionality to the forefront. Subsequently, we identify instructional challenges associated with teaching SJE in the middle grades and share some of the ways in which the teachers in this study navigated these challenges.